Anacardic Acid Isolated From Cashew Nut Shell (Anacardium occidentale) Affects Methane and Other Products in the Rumen Fermentation - A. Saenab; K. G. Wiryawan; Y. Retnani; E. Wina (Media Peternakan, 2017)
Biofat is a hexane extract containing several bioactive compounds with anacardic acid as the major compound. This study aimed to examine the effect of anacardic acid on rumen fermentation, especially methane and its degradation in the in vitro rumen fermentation. The study was arranged in a completely randomized block design. The treatments were control (substrate or complete feed), biofat (substrate + 0.75 uL/mL biofat), and anacardic acid (substrate + 0.75 uL/mL anacardic acid). Measured variables were total gas production, methane, pH, concentration of ammonia (NH3), dry matter degrability (DMD), organic matter degrability (OMD), and neutral detergent fiber degrability (NDFD) in the rumen. The chromatogram GC-MS analysis results indicated that the anacardic acid isolation process of the biofat produced nearly pure isolate (99.44%), and significantly decreased the production of methane by 51.21% and 39.62%, respectively. Anacardic acid degradation pattern in the in vitro rumen test showed a shifting of retention factor (Rf) value after anacardic acid being incubated with the degradation of anacardic acid occurred after 24 h of fermentation. In conclusion, anacardic acid isolated from biofat has a dominant role to reduce the in vitro methane production. Anacardic acid is very potential to be used as a methane reducing agent.